Combined transcriptomic and ChIPseq analyses of the Bordetella pertussis RisA regulon - Loïc Coutte; Rudy Antoine; Stephanie Slupek; Camille Locht (mSystems, 2024)
ABSTRACTThe regulation of Bordetella pertussis virulence is mediated by the two-component system BvgA/S, which activates the transcription of virulence-activated genes (vags). In the avirulent phase, the vags are not expressed, but instead, virulence-repressed genes (vrgs) are expressed, under the control of another two-component system, RisA/K. Here, we combined transcriptomic and chromatin immunoprecipitation sequencing (ChIPseq) data to examine the RisA/K regulon. We performed RNAseq analyses of RisA-deficient and RisA-phosphoablative B. pertussis mutants cultivated in virulent and avirulent conditions. We confirmed that the expression of most vrgs is regulated by phosphorylated RisA. However, the expression of some, including those involved in flagellum biosynthesis and chemotaxis, requires RisA independently of phosphorylation. Many RisA-regulated genes encode proteins with regulatory functions, suggesting multiple RisA regulation cascades. By ChIPseq analyses, we identified 430 RisA-binding sites, 208 within promoter regions, 201 within open reading frames, and 21 in non-coding regions. RisA binding was demonstrated in the promoter regions of most vrgs and, surprisingly, of some vags, as well as for other genes not identified as vags or vrgs. Unexpectedly, many genes, including some vags, like prn, brpL, bipA, and cyaA, contain a BvgA-binding site and a RisA-binding site, which increases the complexity of the RisAK/BvgAS network in B. pertussis virulence regulation.IMPORTANCEThe expression of virulence-activated genes (vags) of Bordetella pertussis, the etiological agent of whooping cough, is under the transcriptional control of the two-component system BvgA/S, which allows the bacterium to switch between virulent and avirulent phases. In addition, the more recently identified two-component system RisA/K is required for the expression of B. pertussis genes, collectively named vrgs, that are repressed during the virulent phase but activated during the avirulent phase. We have characterized the RisA/K regulon by combined transcriptomic and chromatin immunoprecipitation sequencing analyses. We identified more than 400 RisA-binding sites. Many of them are localized in promoter regions, especially vrgs, but some were found within open reading frames and in non-coding regions. Surprisingly, RisA-binding sites were also found in promoter regions of some vags, illustrating the previously underappreciated complexity of virulence regulation in B. pertussis.